Oral History Interview: Earl Hill (1568) - Hill, Earl (My University, 2017)
In his 2015 sessions with Greg Bond, Earl Hill discussed his time at UW as a football player and an undergraduate student in the School of Commerce, as well as his post-collegiate athletic and business careers. Hill discussed growing up, attending high school, and playing athletics at New Rochelle High School in New York. He talked about the college recruiting process and his decision to attend UW. He discussed his athletic and academic transition to UW, and his experiences with freshman and varsity football. He talked about his friendship with Sidney Williams, the LSU-UW football controversy (which he only knew about after the fact), and playing at Miami during his senior year. He discussed playing defense and punting, recalled the improvement of the football team during his time at UW and talked about some highlights from his football career. Hill talked about his academic and social life in Madison and entering the School of Commerce. He talked about his friendships with other athletes and the re-activation of the UW Alpha Phi Alpha chapter so they could participate in intramural athletics. He discussed the difficulty he faced in finding an apartment in Madison in the early 1960s. He discussed his tryout with the Chicago Cardinals of the NFL and a brief stint with British Columbia Lions of the CFL. He talked about his business career, which started at the Social Security Administration and culminated in a job at IBM, first as a salesman in the Office Products Division and then as a Corporate Recruiter for Human Resources. He recalled some racial trouble with a client in Kansas City and the strong support he received from his manager. He discussed his long career at IBM and his college teaching career. This interview was conducted for inclusion in the "African American Athletes at UW" series within the UW-Madison Oral History Program's collection.
Interviewer: Greg Bond
Keywords: Housing; Emory University; Racism; IBM; Chicago Cardinals (NFL); Fraternity/Greek Life; Alpha Phi Alpha; UW-Madison School of Commerce; UW - Miami Football Game (1958); Williams, Sidney; UW - LSU Football Controversy (1956); New Rochelle, NY; UW-Madison Football